Could Resource Rents Finance Universal Access to Infrastructure? A First Exploration of Needs and Rents - Sabine Fuß; Claudine Chen; Michael Jakob; Annika Marxen; Narasimha D. Rao; Ottmar Edenhofer (Fondazione Eni Enrico Mattei (FEEM), 2015)
It is often argued that, ethically, resource rents should accrue to all citizens. Yet in reality the rents from exploiting national resources are often concentrated in the hands of a few. If resource rents were to be taxed, on the other hand, substantial amounts of public money could be raised and used to cover the population's infrastructure needs, such as access to electricity, water, sanitation, communication technology and roads, which all play important roles in a nation's economic development process. Here, we examine to what extent existing resource rents could be used to provide universal access to these infrastructures.
Keywords: H54; 330; Resource Rents; Infrastructure; Economic Development